Stacked dimers of Fe-porphyrin with hydrazine and pyrazine as linkers - Aggarwal, Anshul; Paras; Ramachandran, C.N. (Chemical physics letters, 2021)
[Display omitted] •DFT studies are performed for stacked complexes of metalloporphyrin with and without linkers.•The dimer adopts face-centred or slipped parallel orientation depending on spin state of complex.•Hydrazine and pyrazine linkers lead to an open-jaw like and parallel geometry, respectively.•The absorption maximum of the complex undergoes blue or red shift with a change in the spin state.•Absorption bands undergo bathochromic and hyperchromic shifts when the irons are bridged by linker. Stacking of iron-porphyrin dimers of different spin states is investigated using the dispersion corrected density functional theoretical methods. The studies showed that the dimer adopts a face centered and a slipped parallel stacking in its singlet and nonet spin states, respectively. The effect of linker on stacking revealed that hydrazine linked stacked dimer acquires an open jaw-like geometry, whereas pyrazine linked dimer leads to a symmetrical arrangement with mean planes of two rings parallel. Relative to the monomer, the absorption band of the dimer undergoes blue and red shifts in singlet and nonet spin states, respectively.